Perspectives of patients and healthcare professionals on metabolic monitoring of adult prescribed second-generation antipsychotics for severe mental illness: A meta-synthesis - Poojari, Pooja Gopal; Khan, Sohil; Shenoy, Sonia; Shetty, Sahana; Pai, Keshava; Acharya, Leelavathi D.; Bose, Swarnali; Thunga, Girish (PloS one, 2023)
We conducted a meta-synthesis of qualitative studies to synthesize the views of psychiatric patients on second-generation antipsychotics (SGAs) and the healthcare providers about the metabolic monitoring of adult-prescribed SGAs. A systematic search was conducted in four databases through SCOPUS, PubMed, EMBASE, and CINAHL to identify qualitative studies of patients' and healthcare professionals' perspectives on the metabolic monitoring of SGAs. Initially, titles and abstracts were screened to exclude articles that were not relevant followed by full-text reading. Study quality was assessed by using Critical Appraisal Skills Program (CASP) criteria. Themes were synthesized and presented as per the Interpretive data synthesis process (Evans D, 2002). A total of 15 studies met the inclusion criteria and were analyzed in meta-synthesis. Four themes were identified: 1. Barriers to metabolic monitoring; 2. Patient related concerns to metabolic monitoring; 3. Support system by mental health services to promote metabolic monitoring; and 4. Integrating physical health with mental health services. From the participants' perspectives, barriers to metabolic monitoring were accessibility of services, lack of education and awareness, time/resource constraints, financial hardship, lack of interest on metabolic monitoring, patient capacity and motivation to maintain physical health and role confusion and impact on communication. Education and training on monitoring practices as well as integrated mental health services for metabolic monitoring to promote quality and safe use of SGAs are the most likely approaches to promote adherence to best practices and minimize treatment-related metabolic syndrome in this highly vulnerable cohort. This meta-synthesis highlights key barriers from the perspectives of patients and healthcare professionals regarding the metabolic monitoring of SGAs. These barriers and suggested remedial strategies are important to pilot in the clinical setting and to assess the impact of the implementation of such strategies as a component of pharmacovigilance to promote the quality use of SGAs as well as to prevent and/or manage SGAs-induced metabolic syndrome in severe and complex mental health disorders.